Solar Spectral Irradiance and Summary Outputs Using Excel. (6th February 2015) - Diffey, Brian
Abstract The development of an Excel spreadsheet is described that calculates solar spectral irradiance between 290–3000 nm on an unshaded, horizontal surface under a cloudless sky at sea level, together with summary outputs such as global UV index, illuminance and percentage of energy in different wavebands. A deliberate goal of the project was to adopt the principle of Ockham's razor and to develop a model that is as simple as it can be commensurate with delivering results of adequate accuracy. Consequently, just four inputs are required—geographical latitude, month, day of month and time of day—resulting in a spreadsheet that is easily usable by anyone with an interest in sunlight and solar power irrespective of their background. The accuracy of the calculated data is sufficient for many applications where knowledge of the ultraviolet, visible and infrared levels in sunlight is of interest.